The Study and Compare Good Corporate Governance and Cost of Equity Capital in of Listed Company in the Stock Exchange of Thailand (SET) - อาษาศรี กุณฑีรา (Journal for Developing the Social and Community, 2016)
This research is aimed (1) to study the Corporate Governance Mechanisms and the cost of Equity Capital and (2) to compare the Good Corporate Governance and the cost of Equity Capital of listed companies in Stock Exchange of Thailand (SET). The target populations for this research of listed companies in Stock Exchange of Thailand (SET) 300 firms for the year end 2013. Research design is Empirical Research. The information were gathered financial statements by using SET SMART database. Furthermore, the annual reports (56-1) were analyzed and tested the hypothesis. The statistics for this study were Percentage, Mean, Standard Deviation, Analysis of Variance: ANOVA and Multiple Regression Analysis. The results will be useful information for investors and other. The results 1) the Good Corporate Governance wholly at medium level for the following segments; Proportion of independent Board of directors wholly at high level, Number of meetings of Executive Directors, Director Compensation and Proportion Shareholding Board of directors wholly at medium level, and Merger Board of directors wholly at least level, and the cost of Equity Capital wholly at X = 3.23 S.D. = 429.77 and level for the following segments ; Borrowing Costs 8.23 percentage of Net financial debt, Dividend payout ratio 29.05 percentage of Net profit, The current ratio of current assets -8.47 percentage, The ratio of cash flow to total debt 161.56 percentage 2) The Listed companies in Stock Exchange with different Forms of industry agreed, Total asset with having Good Corporate Governance with different, and listed companies in Stock Exchange with different Forms of industry agreed Total asset, Authorized Capital with having Cost of equity capital had no difference in cost of equity investment at significant level.